The effectiveness of an e‐learning course on medication calculation in nursing students: a clustered quasi‐experimental study. (6th April 2016) - Van Lancker, Aurélie; Baldewijns, Katleen; Verhaeghe, Rik; Robays, Hugo; Buyle, Franky; Colman, Roos; Van Hecke, Ann
Abstract: Aim: To evaluate the effectiveness of an e‐learning course compared with a face‐to‐face lecture on medication calculation. Background: The current knowledge on medication calculation of nursing students and nurses is insufficient to provide safe care. Design: A stratified‐clustered quasi‐experimental study. Methods: A random selection of nursing schools were allocated to the e‐learning course (intervention group) (seven schools; 189 students) or face‐to‐face lecture (control group) (six schools, 222 students). Students in both groups completed a validated medication calculation test (maximum score: 16) prior to the course (T0), immediately after the course (T1) and 3 months later (T2). A linear mixed model was used for data analysis. Results: Medication calculation skills improved significantly more by the face‐to‐face lecture than e‐learning course. Students in both groups significantly improved in medication calculation skills immediately after the course (T1) and 3 months later. The results flattened at T2 with a significant decline in the intervention group between T1 and T2 and a non‐significant decline in the control group. Based on a subgroup analysis, improvement in medication calculation skills at T2 could only be observed in vocational‐level (sub degree) nursing students receiving a face‐to‐face course. Conclusions: Both medication calculation courses had a positive effect on medication calculation skills. Students receiving traditional face‐to‐face lecture improved significantly more than the students receiving the e‐learning course.